2019
DOI: 10.1186/s13045-019-0704-y
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelin is a target of chimeric antigen receptor T cells for treating gastric cancer

Abstract: Background Gastric cancer (GC) is a common cancer in Asia and currently lacks a targeted therapy approach. Mesothelin (MSLN) has been reported to be expressed in GC tissue and could be targeted by chimeric antigen receptor (CAR) T cells. Mesothelin targeting CAR-T has been reported in mesothelioma, lung cancer, breast cancer, and pancreas cancer. However, the feasibility of using anti-MSLN CAR T cells to treat GC remains to be studied. Methods We verified MSLN expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 56 publications
5
87
0
Order By: Relevance
“…All procedures were undertaken under the approval of the Institutional Animal Care and Use Committee of GIBH. NOD-SCID-IL2Rg −/−mice were generated as previously described [20]. To develop the cancer xenograft models, NSI mice aged from 6 to 10 weeks were used.…”
Section: Models For Car-t Cell Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…All procedures were undertaken under the approval of the Institutional Animal Care and Use Committee of GIBH. NOD-SCID-IL2Rg −/−mice were generated as previously described [20]. To develop the cancer xenograft models, NSI mice aged from 6 to 10 weeks were used.…”
Section: Models For Car-t Cell Treatmentmentioning
confidence: 99%
“…We then constructed a third-generation CAR using a humanized single-chain variable fragment (scFv) derived from a mouse anti-human PSCA antibody and a thirdgeneration lentivirus vector composed of a CD3ζ intracellular domain and two costimulatory domains, those of CD28 and DAP10, as previously described [20] ( Fig. 2a).…”
Section: Generation and Characterization Of Anti-psca Car-t Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several CAR-T cell products targeting B cell maturation antigen (BCMA) as well as CD19 are under active clinical trials for RR multiple myeloma [58][59][60]. Several biomarkers such as CLL-1, EGFR, NKG2D, and mesothelin are being targeted in CAR-T cell trials for leukemia and solid tumors [61][62][63][64][65][66]. Dual-target CAR-T cells and sequential or cocktail CAR-T cell trials have been shown to provide clinical benefits for highly refractory cancers [67].…”
Section: Car-t Cells: Living Drugsmentioning
confidence: 99%
“…Currently, low immunogenicity and small volume of scFv have good prospects for cancer therapy. As an example, chimeric antigen receptor T cells comprising anti-mesothelin scFv can redirect T cells to inhibit the growth of gastric cancer [30].…”
Section: Single Chain Variable Fragment (Scfv)mentioning
confidence: 99%